EUTHANASIA DALAM PERSPEKTIF HUKUM PIDANA, ETIKA PROFESI KEDOKTERAN DAN HAK ASASI MANUSIA - Noor Tri Hastuti; Ratna Winahyu Lestari Dewi (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2005)
Euthanasia is an actual issue, that has been a long debate either law or medical world Does a medical doctor permitted to end a patients life, upon the request of a desperate patient because of the long, incurable disease? It is dilemma, indeed but anyhow euthanasia is strongly prohibited in KUHR medical ethics, and against the human rights.